Trametes versicolor as Agent for Delignification of Rice Husks - Laita Nurjanah; Syamsul Falah; Azmi Azhari; Suryani Suryani; I Made Artika (Current Biochemistry, 2014)
Rice husks contains 33.71% w/w lignocelluloses, the most abundantly available raw material on the earth for the production of biofuels and other valuable products. It is comprised of the carbohydrate polymers, cellulose, hemicellulose, and an aromatic polymer, lignin. One of the methods for removing the lignin component of rice husks is by delignification using white-rot-fungi. The aim of the study was to carry out delignification of rice husks using white-rot-fungi. The white-rot-fungi used here were Trametes versicolor and Phanerochaete chrysosporium. The study consisted of a biomass and microbial preparation, chemical assay of the rice husk, ligninase enzyme tests, and delignification of rice husks. Results showed that T. versicolor and P. chrysosporium have ligninase enzyme. The precentage of lignin from the total biomass rice husks was 23.61% w/w, and following the delignification process by T. versicolor for 20 days, the remaining lignin was 16.20% w/w, making the percentage of rice husks lignin degraded as 7.41% w/w. The biodelignification process also decreased the percentage of holocellullose, cellulose, and other extracted substances, and accordingly this increased the percentage of hemicellulose. Based on the ability of T. versicolor to degrade lignin of the rice husk at room temperature (28 ºC) as mentioned above, it can be concluded that T. versicolor has potential to be used for delignification process.